Corporate governance mechanisms and systems - Thomsen, Steen
This exciting new text provides a complete introduction to Corporate Governance. It deals with the control and direction of companies by boards, owners and company law, and also looks at the mechanisms of governance and thedifferent governance systems around the world. Part 1: is a non-technical overview of the relevant theories, governance mechanisms and the country models. Part 2: looks at some of the most important governance mechanisms in detail. Part 3: studies individual international corporate governance systems. Part 4: wraps up with a discussion on governance practices.